Short-term abstinence from alcohol and changes in cardiovascular risk factors, liver function tests and cancer-related growth factors: a prospective observational study - Gautam Mehta; Rajiv Jalan; Matteo Rosselli; James Maurice; Stewart Macdonald; Alexandra Cronberg; Tanya Khera-Butler; Colin Sumpter; Safa Al-Khatib; Anjly Jain; Christos Charalambous; Amir Gander; et al. (BMJ Open)
Objective To assess changes in metabolic risk factors and cancer-related growth factors associated with short-term abstinence from alcohol.Design Prospective, observational study.Setting Single tertiary centre.Participants Healthy subjects were recruited based on intention to: (1) abstain from alcohol for 1 month (abstinence group), or (2) continue to drink alcohol (control group). Inclusion criteria were baseline alcohol consumption >64 g/week (men) or >48 g/week (women). Exclusion criteria were known liver disease or alcohol dependence.Primary and secondary outcome measures The primary outcome was change in insulin resistance (homeostatic model assessment (HOMA) score). Secondary outcomes were changes in weight, blood pressure (BP), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF) and liver function tests. Primary and secondary outcomes were adjusted for changes in diet, exercise and cigarette smoking.Results The abstinence group comprised 94 participants (mean age 45.5 years, SD ±1.2) and the control group 47 participants (mean age 48.7 years, SD ±1.8). Baseline alcohol consumption in the abstinence group was 258.2 g/week, SD ±9.4, and in the control group 233.8 g, SD ±19.0. Significant reductions from baseline in the abstinence group (all p<0.001) were found in: HOMA score (−25.9%, IQR −48.6% to +0.3%), systolic BP (−6.6%, IQR −11.8% to 0.0%), diastolic BP (−6.3%, IQR −14.1% to +1.3%), weight (−1.5%, IQR −2.9% to −0.4%), VEGF (−41.8%, IQR −64.9% to −17.9%) and EGF (−73.9%, IQR −86.1% to −36.4%). None of these changes were associated with changes in diet, exercise or cigarette smoking. No significant changes from baseline in primary or secondary outcomes were noted in the control group.Conclusion These findings demonstrate that abstinence from alcohol in moderate–heavy drinkers improves insulin resistance, weight, BP and cancer-related growth factors. These data support an independent association of alcohol consumption with cancer risk, and suggest an increased risk of metabolic diseases such as type 2 diabetes and fatty liver disease.